Pengaruh Implementasi E-Budgeting, E-Procurement, Komitmen Organisasi, dan Transparansi terhadap Akuntabilitas Keuangan Publik: (Studi Empiris pada Dinas Pemerintah Daerah Kota Palangka Raya Provinsi Kalimantan Tengah) - Novika Ayu Wananda; Yohanes Joni Pambelum; Septa Soraida (GEMILANG: Jurnal Manajemen dan Akuntansi, 2025)
This study aims to analyze the influence of e-budgeting implementation, eprocurement, organizational commitment, and transparency on public financial accountability in the regional government agencies of Palangka Raya City, Central Kalimantan Province. The background of this research is based on the importance of public financial accountability in the era of government digitalization to enhance good regional financial governance. This research uses a quantitative approach with a survey method. Data were collected through questionnaires using a Likert scale, distributed to 72 respondents from 18 government agencies in Palangka Raya City, with each agency represented by 4 respondents. The results of the study show that e-budgeting has no significant effect on public financial accountability, while e-procurement and organizational commitment have a positive and significant effect on public financial accountability. Transparency, however, does not have a significant effect on public financial accountability. Nonetheless, simultaneously, e-budgeting, e-procurement, organizational commitment, and transparency have a significant effect on public financial accountability.